Mucoadhesion studies in the gastrointestinal tract to increase oral drug bioavailability (Revista Brasileira de Ciências Farmacêuticas, 2008)
The oral bioavailability of many drugs can be limited by the residence time of pharmaceutical dosage forms in the gastrointestinal tract. Mucoadhesion has been proposed as a method to increase residence time at a specific area, hence increasing the therapeutic effect of drugs. Most research efforts on mucoadhesion have focused on the stomach and small intestine, with promising results observed from in in vitro studies. However, γ-scintigraphy data obtained in human studies have revealed the lack of success of mucoadhesion approaches in order to increase the contact time of formulations in the upper gut. The lack of in vitro/in vivo correlation can be attributed to the complex nature of the human gastrointestinal tract, with most in vitro models providing little resemblance to the in vivo situation, such as motility, pH, mucus thickness and mucus turnover, presence of enzymes and food. In the colon, the mucus turnover, the sensibility to mucus secretory stimulus and motility are lower than in the stomach and small intestine. Therefore, colonic mucoadhesion may be a more successful approach. Nevertheless, more studies in animals and humans are needed to evaluate its potential, as well as, pharmacokinetic studies to investigate drug release and absorption from mucoadhesive systems.